PENGARUH FEE AUDIT DAN UKURAN PERUSAHAAN KLIEN TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2021-2022 - Cahyaningrum, Hana; Pardistya, Irvan Yoga (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this reaserch is to finding, evaluate, and explain the impact of the cost of testing and the size of the client’s business on the quality of the test. Manufacturing companies listed on the Indonesia Stock Exchange in the eligible food and beverage subsector may meet these requirements. The study is based on secondary data from the Indonesian Stock Exchange for the years 2021-2022. Annual statistical reports can be accessed from the company’s website and the official website of Bursa Indonesia. During two years of research, 17 companies used this sample. Logistic regression analysis is used. Because the dependent variable is dummy, this logistic regression technique is used. These experiments show that the quality of audits is significantly affected by the cost of testing and significantly by the size of the client’s business. Both the size of the client’s business and the audit costs affect the quality of the audit.